Pengaruh Promosi dan Brand Image Terhadap Keputusan Pembelian Pada E-Commerce Lazada Indonesia - Siti Anisa Oktaviani; Lisa Dwinar; Nurul Fadilah Lola Santika; Siti Hafsiah; Muthi Kamila; Muhammad Nadzim; Indah Nur Aliza; Kurniawati Mulyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted with the aim of finding out the influence of promotions and Brand Image on purchasing decisions in Lazada Indonesia e-commerce. The method in this research uses a quantitative method, which means a research process that uses numbers as a tool to analyze Lazada Indonesia purchasing decisions. The type of research in this research uses verification research, namely research that explains cause and effect relationships. The population in this research is all consumers who make purchases at Lazada Indonesia using questionnaire distribution techniques. Brand Image has a positive and significant influence on purchasing decisions on Lazada Indonesia e-commerce.